Integrative purpose of Islamic Education: Semiotic Structural Analysis of Q.S. Al-Alaq 1-5 - Subakat, Rahayu; Nasution, Mustafa Kamal; Ali, Ramsah; Harnedi, Joni (EDUKASIA, 2022)
This study aims to explain the relationship between Q.S. al-'Alaq 1-5 and Islamic education purposes. Philosophically, Q.S. al-'Alaq 1-5 can be used as inspiration for the development of Islamic education. In addition, one of the important points of the education system is the goal or purpose. This library research used data from various Tafsir books of the Qur'an: classical, modern, and contemporary and various literature related to the Islamic education system. The method of data collection was documentation. Data analysis employed transcendental structuralism hermeneutics: descriptive, explanative, discursive, interpretative, and implicative. The results of this study revealed the purposes of Islamic education in Q.S. al-'Alaq 1-5, including 1. spirituality awareness, 2. rationality awareness, 3. ethical awareness, 4. scientific awareness, and 5. social transformation awareness. Thus, in practice, Q.S. al-'Alaq 1-5 can be used as inspiration for the construction of Islamic educational purposes.